Moisture sensor at glass/polymer interface for monitoring of photovoltaic module encapsulants - Carlsson, Thomas; Halme, Janne; Lund, Peter; Konttinen, Petri (Sensors and actuators. A. Physical., 2006)
A sensor developed for measurement of water concentration inside glass/polymer encapsulation structures with a particular application area in accelerated aging of photovoltaic module encapsulants is described. An approximately 5 μm thick porous TiO 2 film applied to a glass substrate with a conductive coating acts as the moisture-sensitive component. The response is calibrated with weather chamber experiments for sensors open to the environment and with diffusion experiments for sensors laminated under an encapsulant. For the interpretation of diffusion experiment results, a transport model describing the diffusion of water across the polymer/TiO 2 interface is developed. The logarithm of AC resistance shows a linear dependence on water concentration in both open and encapsulated calibration. The first measurable response from an encapsulated 3.5 mm × 8 mm size sensor is obtained when approximately 10 μg of water has entered the film. Implications of the calibration results for sensor usage in accelerated aging tests are discussed.